1995
DOI: 10.1063/1.359858
|View full text |Cite
|
Sign up to set email alerts
|

Deep center related to hydrogen and carbon in p-type silicon

Abstract: We have found a hole trap related to hydrogen and carbon in p-type crystalline silicon after hydrogen and deuterium injection by chemical etching and plasma exposure. It was found from deep-level transient spectroscopy that this center is located at 0.33 eV above the valence band and shows no Poole–Frenkel effect in electric fields lower than 6×103 V/cm. The depth profiling technique using deep-level transient spectroscopy indicated that this center is distributed over the range 1–7 μm from the surface with de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 13 publications
3
15
0
Order By: Relevance
“…Recent DLTS experiments [50][51][52]4 suggested that hydrogen can be trapped by C s , forming the E3 defect with an 0/ϩ level at E c Ϫ0.15 eV. The presence of both C and H in the defect was inferred from the variation in the trap concentration with ͓C͔ and ͓H͔.…”
Section: Previous Work On C S -H Complexesmentioning
confidence: 99%
“…Recent DLTS experiments [50][51][52]4 suggested that hydrogen can be trapped by C s , forming the E3 defect with an 0/ϩ level at E c Ϫ0.15 eV. The presence of both C and H in the defect was inferred from the variation in the trap concentration with ͓C͔ and ͓H͔.…”
Section: Previous Work On C S -H Complexesmentioning
confidence: 99%
“…Carbon-hydrogen complexes have previously been studied using conventional deep level transient spectroscopy [7][8][9] ͑DLTS͒. In the present work, we apply high-resolution Laplace deep level transient spectroscopy ͑Laplace DLTS 10 ͒ combined with a uniaxial stress technique to investigate the C-H defect.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, also carbon-hydrogen complexes in silicon have been addressed. [4][5][6][7][8][9][10][11][12][13] The formation of such complexes may significantly reduce the migration of hydrogen and, thus, be of technological importance. So far only a few carbon-hydrogen complexes have been observed by deeplevel transient spectroscopy ͑DLTS͒, 4-6 photoluminescence, 7,8 and infrared-absorption spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The complex, E3, was assigned to a hydrogen atom bound to a C s and located between the carbon atom and one of its four silicon neighbors ͓denoted (C s H BC )Si͔. 5 In p-type silicon a thermally more stable complex, named H1, was observed, 6 which was assigned to a hydrogen atom occupying one of the antibonding sites of C s ͓denoted (H AB C s )Si͔. These complexes have been investigated by ab initio calculations, [11][12][13] and it was found that (C s H BC )Si is the most stable structure for the neutral and positive charge states, whereas (H AB C s )Si is energetically favored for the negative charge state.…”
Section: Introductionmentioning
confidence: 99%